A dynamic strategy-proof algorithm for allocation and pricing of cloud services. (10th May 2019) - Omotehinwa, Temidayo Oluwatosin; Sadiku, Joseph Shuaibu
In this paper, we present a dynamic strategy-proof algorithm for allocation and pricing. The algorithm relies on market history to forecast a benchmark price to ensure truthful valuation from the market participants. The algorithm also ensures that the utility is evenly distributed between buyer and seller. The utility is the difference between the buyer's maximum offer and the seller's minimum acceptable price. The results of the experimental studies carried out shows that: 1) the budget limits of the buyers with successful allocations were not exceeded; 2) only market participants with truthful offers and bids were allocated services; 3) the utility is higher when there is no strategy-proof for preventing overbid and that there is at least a 50% increase in price per unit when there is no strategy-proof to prevent overbid; 4) in terms of computational efficiency, the algorithm converges in polynomial time with a worst-case running time of O(n 2 ).